SARS-CoV-2 post-acute sequelae linked to inflammation via extracellular vesicles - Bachiller, Sara; Vitallé, Joana; Camprubí-Ferrer, Lluís; García, Manuel; Gallego, Isabel; López-García, Marina; Galvá, María Isabel; Cañizares, Julio; Rivas-Jeremías, Inmaculada; Díaz-Mateos, María; Gasca-Capote, Carmen; Moral-Turón, Cristina; et al. (Frontiers in Immunology, 2025)
BackgroundDespite the efficacy of SARS-CoV-2 vaccines in reducing mortality and severe cases of COVID-19, a proportion of survivors experience long-term symptoms, known as post-acute sequelae of SARS-CoV-2 infection (PASC). This study investigates the long-term immunological and neurodegenerative effects associated with extracellular vesicles (EVs) in COVID-19 survivors, 15 months after SARS-CoV-2 infection.Methods13 Controls and 20 COVID-19 survivors, 15 months after SARS-CoV-2 infection, were recruited. Pro-inflammatory cytokines were analyzed in both plasma and EVs. A deep-immunophenotyping of monocytes, T-cells and dendritic cells (DCs) was performed, along with immunostainings of SARS-CoV-2 in the colon.ResultsHigher concentrations of pro-inflammatory cytokines and neurofilaments were found in EVs but not in plasma from COVID-19 survivors. Additionally, COVID-19 participants exhibited altered monocyte activation markers and elevated cytokine production upon lipopolysaccharide stimulation. Increased activation markers in CD4+ T-cells and decreased indoleamine 2,3-dioxygenase expression in DCs were observed in COVID-19 participants. Furthermore, the amount of plasmacytoid DCs expressing β7-integrin were higher in COVID-19, potentially associated with the viral persistence observed in the colon.ConclusionsCOVID-19 survivors exhibit long-term immune dysregulation and neurodegeneration, emphasizing the need for ongoing monitoring of PASC. The cargo of EVs can be a promising tool for early detection of virus-induced neurological disorders.